Men and Woman as Victims of Patriarchy in Ika Natassa’s Books: Critical Eleven & Divortiare Trilogy - Yogie Rukwanda; Setefanus Suprajitno (Kata Kita: Journal of Language, Literature, and Teaching, 2023)
In this paper we intend to analyze the victimization of patriarchy toward two genders at the same time, male and female, that previously was only considered as a system that oppresses women due to its characteristics that put men in a more superior position. We analyze the behavior of the main characters from two Ika Natassa’s books Critical Eleven and Divortiare Trilogy that allegedly embody the patriarchal values in their behaviors on a daily basis that later could victimize them in its practice. In analyzing the books, we use the traditional Javanese patriarchy values such as 3M, kanca wingking, and benggol & bonggol. We divide the analysis  into two parts. In the first part, we analyze how patriarchal ideology affects the lives of the two main female characters, Alex and Anya, where they had to keep up with the expectations of becoming the ideal traditional wife and how it put them in hard times. In the next part, we analyze how the patriarchal ideology surprisingly also affects the husbands of the main female characters. The finding shows that patriarchal ideologies surprisingly oppresses not only the wives but the husbands as well.